Оцінка скоротливої функції міокарду та показників системної запальної відповіді при гіпертонічній хворобі у поєднанні з хронічним обструктивним захворюванням легень під впливом терапії - Яценко, Олег Вадимович; Яценко, О. В.; Yatsenko, O. V. (My University, 2017)
Патогенетичні зв'язки гіпертонічної хвороби і хронічного обструктивного захворювання легень є мало вивченим. За результатами декількох досліджень у пацієнтів з хронічним обструктивним захворюванням легень кардіоваскулярні причини складають біля 25% смертності. Функція правого шлуночка є найважливішим детермінантом довголіття у пацієнтів з легеневою артеріальною гіпертензією. Мета дослідження полягала у вивченні показників деформації міокарду правого шлуночка та показників системної запальної відповіді під впливом терапії. Матеріали та методи дослідження. Обстежені 38 хворих на хронічне обструктивне захворювання легень 2–3 стадії у фазу загострення на тлі гіпертонічної хвороби, Всім пацієнтам проводили, спірографічне ехокардіографічне дослідження, визначення рівнів ММП-9 і вч-СРБ, ЕТ-1 в плазмі крові. Аналіз отриманих даних продемонстрував, що через 24 тижні лікування розувастатином та амлодипіном було відмічено достовірне зниження показників Ендотеліну-1 високочутливого С-реактивного білку матриксної металлопротеїнази - 9 під час приймання терапії у порівнянні з групою яка отримувала стандартну схему терапії. Та достовірне покращення повздовжньої деформації міокарду правого шлуночка в основній групі на 6,54. Додавання додаткової терапії амлодипіном та розувастатином у хворих на гіпертонічну хворобу у поєднанні з хронічним обструктивним захворюванням легень достовірне покращує деформуючі функції міокарду правого шлуночка. Доведено достовірне зниження біохімічних маркерів. Патогенетические связи гипертоничекой болезни и хронического обструктивного заболевания легких являются мало изученными. По результатам нескольких исследований у пациентов с хроническим обструктивным заболеванием легких кардиоваскулярные причины смерти составляют около 25%. Медичні науки 124 Український журнал медицини, біології та спорту – № 6 (8) Функция правого желудочка является важнейшим детерминантом долголетия у пациентов с легочной артериальной гипертензией. Цель исследования заключалась в изучении показателей деформации миокарда правого желудочка и показателей системного воспалительного ответа под влиянием терапии. Обследованы 38 больных с хроническим обструктивным заболеванием легких 2-3 стадии в фазу обострения на фоне гипертонической болезни, которые были разделены на две подгруппы. В контрольную подгруппу включены 19 пациентов принимавших стандартную терапию, в основную группу составили 19 пациентов которым к стандартной терапии были назначены розувастатин в дозе 20 мг и амлодипин 5 мг. Всем пациентам проводили спирографическое исследование, эхокардиографическое исследование, определение уровней ММП-9 и вч-СРБ, ЕТ-1 в плазме крови. Анализ полученных данных показал, что через 24 недели лечения розувастатином и амлодипином было отмечено достоверное снижение показателей Эндотелина 1, высокочувствительного С-реактивного белка, матриксной металлопротеиназы -9. Достоверно улучшение продольной деформации миокарда правого желудочка в основной группе на 6,54% в сравнении с контрольной. Добавление дополнительной терапии амлодипином и розувастатином у больных с гипертонической болезнью в сочетании с хроническим обструктивным заболеванием легких достоверно улучшает деформирующие функции миокарда правого желудочка. Доказано достоверное снижение биохимических маркеров в подгруппе больных с гипертонической болезнью и хроническим обструктивным заболеванием легких, которым дополнительно назначено терапию амлодипином и розувастатином. Pathogenic connections of hypertension and chronic obstructive pulmonary disease (COPD) are poorly understood. According to several studies in patients with COPD, the cardiovascular causes of death are about 25%. The function of the right ventricle is the most important determinant of longevity in patients with pulmonary arterial hypertension. The most evidence-based inflammatory marker, which closely connected with exponential function of external respiration, is the C-reactive protein. Matrix metalloproteinases-9 plays an important role in cardiovascular diseases, providing stabilization of atherosclerotic plaque. The purpose of the study was to examine the parameters of right ventricular myocardium deformation and systemic inflammatory response indices under the influence of therapy. Materials and methods. 38 patients with COPD 2-3 stages in the acute phase against the background of hypertension, which were divided into two subgroups, were examined. The control subgroup included 19 patients taking standard therapy, the main group included 19 patients with a comorbid course of COPD 2-3 st. and GB 2 stage, to which standard therapy was prescribed rosuvastatin in a dose of 20 mg and amlodipine 5 mg. All patients underwent a general examination, collection of complaints and anamnesis, spirographic research to determine the parameters of the function of external respiration, echocardiographic study, determination of MMP -9 and hr-CRP, ET-1 levels in blood plasma. Results and discussion. Analysis of the obtained data showed that after 24 weeks of treatment with rosuvastatin and amlodipine, there was a significant decrease in Endothelin 1 (-64.69 [-74.06, -57.77] Δ% vs. -48.26 [-58.87, -20 48 ] Δ%), high-sensitivity C-reactive protein -70.00 [-80.00; -66.67] Δ% against -60.00 [-66.67; -42.86], matrix metalloproteinase -9 (-57.54 [-66.84, -49.07] Δ% vs. -47.84 [-62.13, -38.65] Δ%, respectively) when taking therapy compared to the group receiving the standard therapy regimen. Significant improvement in longitudinal deformation of the myocardium of the prostate in the main group by 6.54% in comparison with the control (-17.90 [-17.55, -18.30]% vs. -16.80 [-15.90, -17.80]%). Conclusions. Additional therapy with amlodipine and rosuvastatin in patients with GB in combination with COPD significantly improves the myocardium deforming functions of the prostate as compared to the subgroup of patients with GB and COPD on the background of standard therapy. A significant decrease in biochemical markers: Endothelin-1, a highly sensitive C-reactive protein, and matrix metalloproteinase-9 in a subgroup of patients with GB and COPD was additionally prescribed therapy with amlodipine and rosuvastatin.
Оценка сократительной функции миокарда и показателей системного воспалительного ответа при гипертонической болезни в сочетании с хроническим обструктивным заболеванием легких под влиянием терапии
Evaluation of Myocardium Contractile Function and Systemic Inflammatory Response Indices in Hypertensive Disease in Combination with Chronic Obstructive Pulmonary Disease in the Process of Treatment
Keywords: гіпертонічна хвороба; хронічне обструктивне захворювання легень; лікування; біомаркери; гипертоническая болезнь; хроническое обструктивное заболевание легких; лечение; биомаркеры; hypertension; chronic obstructive pulmonary disease; treatment; biomarkers